Tarybų Lietuvos bibliotekų istorijos Didžiojo Tėvynės karo metais šaltinių ir tyrinėjimų klausimu - Sinkevičius, Klemensas (Knygotyra, 2026)
The history of Soviet Lithuania’s libraries during the Great Patriotic War is a part of the Soviet Union’s library history. It investigates the library service to the evacuees from Lithuania, the dissemination of the Communist press in the territory occupied by the Hitler army, the damages inflicted to the libraries by the invaders and the restoration of the libraries after the liberation of the country. Studying this period one meets difficulties as the archival documents are very sparse and the memoiristic materials are still not collected and analyzed.